Apakah Kurva Phillips Eksis Pada Perekonomian Indonesia di Masa Pandemi Covid-19? - Ernawati Ernawati; Mansyur Asri (Journal of Business and Economics Research (JBE), 2022)
The Covid-19 pandemic has resulted in low demand for goods and services. The price level tends to be low. Meanwhile, the unemployment rate tends to be high due to weak demand. This condition appears to be in line with Phillips' view of the trade-off between the inflation rate and unemployment. This study aims to examine whether the Phillips curve phenomenon applies to the Indonesian economy during the Covid-19 pandemic. The research data was obtained from the publication of the Statistics Indonesia (BPS) with 34 provinces of analysis unit, period 2020. The data were analyzed using correlation and difference tests. The results show that the Phillips curve does not exist for the case of Indonesia nationally, but only exists in the Eastern Region of Indonesia. The results also show that there is no significant difference between inflation and unemployment rates in the group of provinces that implement Large-Scale Social Restrictions (pembatasan sosial berskala besar, PSBB) during the pandemic and those that do not implement PSBB. This paper recommends a more streamlined coordination of monetary and fiscal policies with the goal of achieving price stability for monetary policy and reducing unemployment for fiscal policy